2020
DOI: 10.1007/978-3-030-41593-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of m-Government: Perspectives from a Namibian Marginalised Community

Abstract: Mobile-government (m-Government) services adoption is being advanced as an alternative solution for addressing challenges faced by electronic-government (e-Government) adoption in marginalised communities. However, factors of m-Government need to be understood if it is to be adopted by marginalised communities. There are suggestions that many contextual factors affect to the adoption of m-Government services. In this study, factors of m-Government in Oniipa, a marginalised rural community in Namibia are resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
2
7
0
2
Order By: Relevance
“…This finding implies that users place a higher premium on the trust in the system than on the other factors proposed in this study. This finding corroborates with other studies conducted in other developing countries whereby perceived lack of trust in system had an impact on the success of the systems in various countries such as South Africa (Bayaga and Ophoff, 2019), Namibia (Frohlich et al , 2020) and Kenya (Otieno and Omwenga, 2015). In Rwanda, for instance, users could not use the systems effectively due to worries that IT technicians could intrude in the systems by bypassing the authentication process and making changes to the information (Mukamurenzi et al , 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding implies that users place a higher premium on the trust in the system than on the other factors proposed in this study. This finding corroborates with other studies conducted in other developing countries whereby perceived lack of trust in system had an impact on the success of the systems in various countries such as South Africa (Bayaga and Ophoff, 2019), Namibia (Frohlich et al , 2020) and Kenya (Otieno and Omwenga, 2015). In Rwanda, for instance, users could not use the systems effectively due to worries that IT technicians could intrude in the systems by bypassing the authentication process and making changes to the information (Mukamurenzi et al , 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In Rwanda, for instance, users could not use the systems effectively due to worries that IT technicians could intrude in the systems by bypassing the authentication process and making changes to the information (Mukamurenzi et al , 2019). In Namibia, users indicated that they would prefer to go to the government office instead of using mobile applications to access government services due to the lack of trust in the system (Frohlich et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It implies that users perceive the system to have features that enhances security and privacy of their data. This finding was in line with other studies conducted in South Africa (Bayaga & Ophoff 2019), Namibia (Frohlich et al 2020), Kenya (Otieno & Omwenga 2015), and Rwanda (Mukamurenzi et al 2019). In Rwanda, for instance, the lack of trust affected the success of the electronic government system (Mukamurenzi et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, it was found that some users were worried that IT technicians may be bypassing the authentication process and making changes to the information. In Namibia, users preferred to walk into a government office instead of accessing governmental services via mobile applications because of worries of trust in system (Frohlich et al 2020). As the GePG system requires users to provide personal details, it is important for the ministry to take necessary technical and procedural measures to ensure that the system is secured and data cannot be accessed by unauthorised users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation